2018
DOI: 10.1007/s00382-018-4158-7
|View full text |Cite
|
Sign up to set email alerts
|

The future of coastal upwelling in the Humboldt current from model projections

Abstract: The Humboldt coastal upwelling system in the eastern South Pacific ocean is one of the most productive marine ecosystems in the world. A weakening of the upwelling activity could lead to severe ecological impacts. As coastal upwelling in eastern boundary systems is mainly driven by wind stress, most studies so far have analysed wind patterns change through the 20th and 21st Centuries in order to understand and project the phenomenon under specific forcing scenarios. Mixed results have been reported, and analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 70 publications
6
40
0
Order By: Relevance
“…This study confirms that HAB dynamics in the Ecuadorian coastal zone seem to be constrained by the Humboldt upwelling system, high precipitation, and terrestrial nutrients from the Guayas Basin, aligning with other HAB studies in coastal ecosystems and upwelling zones (Kudela et al, 2005;Vila and Masó, 2005;Borbor-Cordova et al, 2006;Anderson et al, 2017;Oyarzún and Brierley, 2018). In addition, high sea surface temperature during ENSO and ocean heat waves seem to affect all the aforementioned drivers, along with the adaptive strategies of the phytoplankton species and their community assemblage (Masó and Garcés, 2006;Anderson, 2014;Anderson et al, 2017).…”
Section: Oceanography Of Habs and Remote Sensing Datasupporting
confidence: 90%
See 2 more Smart Citations
“…This study confirms that HAB dynamics in the Ecuadorian coastal zone seem to be constrained by the Humboldt upwelling system, high precipitation, and terrestrial nutrients from the Guayas Basin, aligning with other HAB studies in coastal ecosystems and upwelling zones (Kudela et al, 2005;Vila and Masó, 2005;Borbor-Cordova et al, 2006;Anderson et al, 2017;Oyarzún and Brierley, 2018). In addition, high sea surface temperature during ENSO and ocean heat waves seem to affect all the aforementioned drivers, along with the adaptive strategies of the phytoplankton species and their community assemblage (Masó and Garcés, 2006;Anderson, 2014;Anderson et al, 2017).…”
Section: Oceanography Of Habs and Remote Sensing Datasupporting
confidence: 90%
“…On the other hand, this study suggests that upwelling systems are related to HABs in the Gulf of Guayaquil. The Humboldt upwelling system is considered to be one of the most productive systems globally (Daneri et al, 2000;Taylor, 2008;Oyarzún and Brierley, 2018). Research groups, such as GEOHAB (Hallegraeff, 2004), have highlighted the potential impacts of HABs on upwelling systems in the context of climate change (Kudela et al, 2005;Edwards et al, 2006;Wei et al, 2008;Trainer et al, 2010;Díaz et al, 2016;Pitcher et al, 2017).…”
Section: Oceanography Of Habs and Remote Sensing Datamentioning
confidence: 99%
See 1 more Smart Citation
“…the world (Chavez et al, 2002;Pennington et al, 2006;Oyarzún and Brierley, 2018). In this study, highest concentrations of dinoflagellates were found in Manta (April 2017), La Libertad (March 2015), and Puerto Bolivar (May 2014 and May 2017), during wet season.…”
Section: Environmental Variables and Seasonalitymentioning
confidence: 45%
“…However, a majority of models show suppressed IOD activity under the warming scenarios corresponding with the reduced temperature variability over the Arabian Sea upwelling (Fig. 2), which may be a response to the increased ocean stratification seen in the transient simulations (Oyarzún and Brierley, 2019). In the tropical Atlantic, weak but negative trends for the AMM (Fig.…”
Section: Changes In Sst-based Modesmentioning
confidence: 96%